DAMPAK PERUBAHAN IKLIM TERHADAP SEKTOR PERTANIAN DAN EKONOMI DI DESA SIDOMULYO - Ruliyansa, Ruliyansa (AKTUAL, 2024)
Climate change has become a global issue that not only affects the environment, but also has a significant impact on the agricultural sector and economy, especially in developing countries like Indonesia. This research aims to analyze the impact of climate change on agricultural productivity and its implications for the regional economy, with a focus on the conditions faced by farmers in areas that are vulnerable to climate change. The method used in this research is a descriptive qualitative approach. Data collection was carried out through in-depth interviews with farmers, weather observers and stakeholders in the agricultural sector, as well as participant observation from various relevant sources. With this approach, it is hoped that a more comprehensive understanding of the dynamics occurring in the field can be obtained. The research results show that changes in rainfall patterns, such as shifts in the rainy season and an increase in extreme rainfall, along with a significant increase in temperature, have caused a decrease in crop productivity or crop yields. This impact is not only felt directly on farmers’ income, but also affects food security at the regional level, which could result in a food crisis in the future. Through this research, it is hoped that it can make a meaningful contribution in formulating strategies to face the challenges posed by climate change in the agricultural and economic sectors. By preparing farmers and agricultural communities to adapt, we can create greater resilience to the negative impacts of climate change, as well as ensure the sustainability of agricultural production which is important for the national economy.